UPAYA MENINGKATKAN HASIL BELAJAR SISWA MATEMATIKAMELALUI PENERAPAN METODE BELAJAR AKTIF MODEL MENINJAU KEMBALI KESULITAN DI KELAS II SDN 009 TANJUNG PALAS - Sulastri, Jus (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
This study aimed to describe the results of learning through the use of media folder. The subject of research grade II SDN 009 Tanjung Palas. Improved learning outcomes in terms of four categories of goods, namely absorption, the effectiveness of learning, mastery learning completeness students both individually and classical completeness and accuracy of the results of learning. The instrument used for data collection is an oral test and a written test in the form of worksheets performed after the learning process. Results Shows absorption learning outcomes on average 83% is considered very good, very effective learning effectiveness categorized with an average of 70. While the completeness of student learning outcomes Presented complete 100%. In addition, increase the thoroughness of students in each cycle, the first cycle (58.82%), the second cycle (70.59%), the third cycle (88.24%). Based on these results it can be concluded that through active learning model of revisiting the difficulty can improve students' mathematics learning outcomes.